Denial of Treatment to Obese Patients-the Wrong Policy on Personal Responsibility for Health - Nir Eyal (Kerman University of Medical Sciences, 2013)
In many countries around the world, including Iran, obesity is reaching epidemic proportions. Doctors have recently taken, or expressed support for, an extreme 'personal responsibility for health' policy against obesity: refusing services to obese patients. This policy may initially seem to improve patients' incentives to fight obesity. But turning access to medical services into a benefit dependent on health improvement is a bad policy. It conditions the very aid that patients need in order to become healthier or success in becoming healthier. Whatever else we may think of personal responsibility for health policies, this particular one is absurd. Unfortunately, quite a few personal responsibility for health policies use similar absurd conditioning. They mistakenly use 'carrots' or 'sticks' for adherence the basic means to the same health outcomes that they seek to promote. This perspective proposes the following rule of thumb: any conditional incentive for healthy choice should be in a currency other than the basic means to that healthy choice.